The Crossing Numbers of Join of Some Graphs with n Isolated Vertices - Ding Zongpeng (Discussiones Mathematicae Graph Theory, 2018)
There are only few results concerning crossing numbers of join of some graphs. In this paper, for some graphs on five vertices, we give the crossing numbers of its join with n isolated vertices.